BASICS OF DEVELOPMENT OF NEW ANTIFUNGAL AGENTS IN OPHTHALMOLOGY: A REVIEW - KURGUZOV, ILYA; LOGUNKOVA, IRINA; BAKHRUSHINA, ELENA; DURZHINSKAYA, MADINA; PLYUKHOVA, ANNA; KURGUZOVA, ALEXANDRA; NARBUT, MARIA (International Journal of Applied Pharmaceutics, 2026)
The aim of this work was to study the status of treatment of fungal eye infections. Recent data indicate a steady rise in diagnosed cases of fungal ocular diseases, particularly fungal keratitis-especially in developing countries. In some regions, the absence of locally available antifungal medications, despite increasing demand, contributes to this trend. Despite prolonged observation and efforts to combat fungal eye diseases, the global availability of antifungal drugs remains limited, especially for local use. These drugs are an integral part of comprehensive treatment, along with systemic drugs. The objective of this review work is to conduct a comparative analysis of molecules that have been evaluated in terms of antifungal activity, bioavailability, efficacy, and safety, considering the long duration of treatment and, consequently, increased risks of side effects. For this purpose, a comprehensive review was conducted of materials published between 2015 and 2025 in international scientific databases, including PubMed, Scopus, Google Scholar, and ResearchGate. The search strategy was designed to capture relevant studies on antifungal ophthalmic therapies, dosage forms, and active pharmaceutical ingredients used in the treatment of fungal keratitis. Based on the reviewed literature, a SWOT analysis was performed, for the first time in this context, to systematically evaluate the strengths, weaknesses, opportunities, and threats associated with the principal dosage forms of ophthalmic antifungal drugs. This novel analytical approach enabled the identification of key directions for enhancing therapeutic efficacy, improving formulation design, and addressing clinical and regulatory gaps in the management of fungal ocular infections. The presented data can serve as a foundation for the development of improved drug formulations and delivery systems targeted directly to the affected ocular tissues-without preservatives, with controlled drug release-thereby enhancing treatment effectiveness, minimizing drug loss, and reducing patient risks associated with side effects and antifungal resistance. Furthermore, these advancements have the potential to significantly improve patient quality of life and increase the likelihood of full recovery, without irreversible visual impairment. For this purpose, a comprehensive review was conducted of materials published between 2015 and 2025 in international scientific databases, including PubMed, Scopus, Google Scholar, and ResearchGate. The search strategy was designed to capture relevant studies on antifungal ophthalmic therapies, dosage forms, and active pharmaceutical ingredients used in the treatment of fungal keratitis. Based on the reviewed literature, a SWOT analysis was performed, for the first time in this context, to systematically evaluate the strengths, weaknesses, opportunities, and threats associated with the principal dosage forms of ophthalmic antifungal drugs. This novel analytical approach enabled the identification of key directions for enhancing therapeutic efficacy, improving formulation design, and addressing clinical and regulatory gaps in the management of fungal ocular infections. The presented data can serve as a foundation for the development of improved drug formulations and delivery systems targeted directly to the affected ocular tissues-without preservatives, with controlled drug release-thereby enhancing treatment effectiveness, minimizing drug loss, and reducing patient risks associated with side effects and antifungal resistance. Furthermore, these advancements have the potential to significantly improve patient quality of life and increase the likelihood of full recovery, without irreversible visual impairment.